Heterogeneity and breadth of host antibody response to KSHV infection demonstrated by systematic analysis of the KSHV proteome. - Nazzarena Labo; Wendell Miley; Vickie Marshall; William Gillette; Dominic Esposito; Matthew Bess; Alexandra Turano; Thomas Uldrick; Mark N Polizzotto; Kathleen M Wyvill; Rachel Bagni; Robert Yarchoan; et al. (PLoS Pathogens)
The Kaposi sarcoma associated herpesvirus (KSHV) genome encodes more than 85 open reading frames (ORFs). Serological evaluation of KSHV infection now generally relies on reactivity to just one latent and/or one lytic protein (commonly ORF73 and K8.1). Most of the other polypeptides encoded by the virus have unknown antigenic profiles. We have systematically expressed and purified products from 72 KSHV ORFs in recombinant systems and analyzed seroreactivity in US patients with KSHV-associated malignancies, and US blood donors (low KSHV seroprevalence population). We identified several KSHV proteins (ORF38, ORF61, ORF59 and K5) that elicited significant responses in individuals with KSHV-associated diseases. In these patients, patterns of reactivity were heterogeneous; however, HIV infection appeared to be associated with breadth and intensity of serological responses. Improved antigenic characterization of additional ORFs may increase the sensitivity of serologic assays, lead to more rapid progresses in understanding immune responses to KSHV, and allow for better comprehension of the natural history of KSHV infection. To this end, we have developed a bead-based multiplex assay detecting antibodies to six KSHV antigens.